2021
DOI: 10.1186/s40510-021-00389-x
|View full text |Cite
|
Sign up to set email alerts
|

Mandibular incisor inclination and gingival recession after treatment with the Jasper Jumper: a 10-year follow-up

Abstract: Objective To evaluate the long-term outcomes of Class II treatment with the Jasper Jumper appliance and comprehensive orthodontic treatment concerning inclination of the mandibular incisors and gingival recession. Methods Sixteen patients with Class II malocclusion at a mean age of 12.54y (SD = 1.17) were treated with the Jasper Jumper appliance and comprehensive orthodontic treatment. The mean treatment time was 2.05y (SD = 0.21). Dental records w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 39 publications
0
1
0
2
Order By: Relevance
“…We also observed that, in relation to the subcategory Smile with Mouth corridors subcategory [9] (Figure 2), only 2 individuals (4%) drew this type of smile in M1 and only 1 individual (2%) drew this type of percept in M2.…”
Section: Resultssupporting
confidence: 52%
“…We also observed that, in relation to the subcategory Smile with Mouth corridors subcategory [9] (Figure 2), only 2 individuals (4%) drew this type of smile in M1 and only 1 individual (2%) drew this type of percept in M2.…”
Section: Resultssupporting
confidence: 52%
“…In the present study, dental casts were digitized usinga 3D extraoral scanner to obtain STL (stereolithography:standard triangulation language) files viaCAD/CAM technology, which allows the surface data of the dental arches to be saved on the computer asthree-dimensional images [ 11 , 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, dental casts were digitized usinga 3D extraoral scanner to obtain STL (stereolithography:standard triangulation language) files viaCAD/CAM technology, which allows the surface data of the dental arches to be saved on the computer asthreedimensional images [11][12][13].…”
Section: Discussionmentioning
confidence: 99%